Peningkatan Kapasitas Masyarakat melalui Pengolahan Limbah Organik untuk Pupuk Tanaman di Pekarangan Perkotaan - Siti Nurul Rofiqo Irwan; Nasih Widya Yuwono; Retno Nur Utami; Haviah Hafidhotul Ilmiah (Institut Pertanian Bogor, 2023)
The most sources of waste have been from households in urban area. The urban high population and daily food consumption effect the waste is potential to pollute the environment. Innovation of waste treatment should be applied by local community in urban area to reduce the household waste. This activity was a community service program UGM 2022 and supporting the Bantul Government program